Penyuluhan tentang CERDIK dalam Upaya Pencegahan Penyakit Tidak Menular pada Siswa SMA Negeri 6 Kota Manado - Ottay, Ronald Imanuel; Pali, Cicilia; Kuhon, Frelly Valentino; Sumampouw, Oksfriani Jufri; Nelwan, Jeini Ester (Nawasena Bhakti, 2025)
Background: Non-Communicable Diseases (NCDs) can be prevented by promoting the CERDIK behavior in daily life. The CERDIK behavior consists of several key actions: regular health check-ups, avoiding cigarette smoke, engaging in physical activity, maintaining a balanced diet, getting adequate rest, and managing stress. The aim of this activity was to provide health education focused on the prevention of NCDs, targeting students of SMAN 6 Kota Manado. Adolescents were chosen as the primary audience to raise early awareness and encourage the implementation of CERDIK behavior from a young age. Methods: This activity was conducted on Friday, September 6, 2024, starting at 08:00 AM until completion. Health education was delivered by Dr. Ronald I. Ottay, M.Kes, and a team of master's students from the public health sciences program. The session lasted for two hours and concluded with a friendly gathering. A total of 60 students and teachers participated in the event. Pre- and post-educational assessments were conducted to measure changes in knowledge levels among the participants. Results: The results of this activity showed that the total knowledge score increased from 625 before the session to 670 afterward, indicating a gain of 45 points. The average score increased from 35.2 to 38.7, showing a 3.5-point improvement. This indicates a noticeable difference in knowledge scores before and after the health education session. Conclusion: This community service activity demonstrated that the educational intervention had a positive impact on students' knowledge regarding the prevention of non-communicable diseases through the implementation of CERDIK behavior at SMAN 6 Manado.